Behavioral Factors Determining Interest in Using Online Loans Generation Z: a Study in Indonesia - Riyanto, Fery; Purusa, Nanda Adi; Zakaria, Fakhmi; Chaichotchuang, Ekarat (Universitas Dian Nuswantoro Semarang, 2025)
The development of fintech lending or better known as online loans (pinjol) has shown a significant increase in the last two years. The largest users are millennials and Z generations, reaching 57.3 percent compared to other user ages. This study aims to see behavioral factors, namely financial literacy, emotions, attachment, materialism, and risk perception that influence interest in online loans among Generation Z. The research population is Generation Z in Indonesia, especially in Central Java Province. The sampling technique used is purposive sampling which obtained 285 samples. Data analysis of the study used the Partial Least Square (PLS) method with Smart-PLS 3 software. The results of the study show that first, Financial Literacy does not have a negative effect on interest in online loans. Second, Emotions have a positive effect on interest in online loans. Third, Attachment has a positive effect on interest in online loans. Fourth, Materialism has a positive effect on interest in online loans. Fifth, Risk perception has a positive effect on interest in online loans.